Planudes y el libro XII de la Antología Palatina (Argos, 2025)
In this paper, we analyze the 16 epigrams of Anthologia Palatina XII that also appear in the amatoria section of Anthologia Planudea. We try to determine what criteria (particularly of sexual and moral censorship) and what authors were used by Planudes in his selection.
Keywords: Greek Anthology; Maximus Planudes; censorship; Strato of Sardis; homoerotism